Cellular adaptations of the heart muscle to exercise training - Moore, R. L. (Annals of Medicine, 1998)
Exercise training is unique in that it represents a stress that elicits positive adaptations in the heart. Hallmark adaptations of the heart to training include resting and submaximal exercise bradycardia, increases in end-diastolic dimension, improved ventricular function, and an increase in the resistance of the heart to ischaemic insult. Endurance exercise training has also been shown to be effective in the treatment and/or prevention of the cardiac functional deficits that are known to occur in settings of chronic hypertension, advanced age, and myocardial infarction. Over the last 20-25 years, considerable effort has been directed towards identifying the cellular basis for the global adaptations of the normal and pathologically involved heart to endurance exercise training. It is the intent of this brief review to identify some of the known and hypothetical cellular adaptations that underlie the positive effects of endurance exercise training on the heart.